A systematic review on technological interventions toa id the mental health of university students (Research, Society and Development, 2022)
Mental disorders are increasingly common in university students, since this population has several insecurities and concerns at this stage of life, which makes them prone to developing these types of diseases. Despite this, few students seek help for fear of the stigma it can bring, in addition to the few resources available for treatment within the university. Treatment through apps or websites can be an innovative and promising way of offering treatment to this population. Therefore, this article aims to show the result of a systematic literature review of studies in which mobile applications or websites were used to promote mental health interventions for university students. Among the selected studies, bibliometric analyzes and content analysis were carried out, where it was identified that most interventions were carried out through mobile applications, seeking to treat mainly anxiety and depression, using psychological approaches such as cognitive behavioral therapy with great frequency. (CBT) and mindfulness. It was concluded that there are many interventions that are tested on university students, but there are few that are developed especially for this audience.